Relationship between frailty, prognostic scores, and functional tests in elderly patients with chronic obstructive pulmonary disease (Research, Society and Development, 2025)
Introduction: The aging of the population has raised concerns about the health conditions of the elderly and the relationship with their functional capacity. The present study aims to present an evaluation of the relationship between frailty and prognostic scores and functional tests in elderly patients with chronic obstructive pulmonary disease. The impact of frailty on the clinical and functional control of COPD has been investigated and there are already recommendations for early management of these patients. Methodology: Comparative analyses between the groups were performed using the unpaired t-test, Mann-Whitney test, Chi-square test and Chi-square test via Monte Carlo simulation, and Fisher's exact test. Brightness analyses between the Frailty Indicator (IVCF) and the other variables were performed using Pearson's Correlation Coefficient. A confidence level of 80% (CI80%) was chosen, corresponding to an α error of 0.20. This choice was motivated by the limitations of the reduced team and the short time available for data collection. Results: According to the data obtained, the increase in IVCF (greater frailty) was correlated with lower performance in the 6MWT (r=-0.35; p=0.041), lower FEV1 (r=-0.38; p=0.026) and reduction in total lung capacity (FVC) (r=-0.35; p=0.039). The IVCF also showed positive correlations between the presence of frailty and moderate to severe symptoms, with a higher CAT score (r=0.59; p=0.000) and worsening of the prognosis with higher numbers in the BODE index (r=0.35; p=0.038). Conclusion: Frail patients screened by IVCF have worse clinical and functional conditions than non-frail patients.